Narrow lpa1 Metaxylems Enhance Drought Tolerance and Optimize Water Use for Grain Filling in Dwarf Rice - Priatama, Ryza A.; Heo, Jung; Kim, Sung Hoon; Rajendran, Sujeevan; Yoon, Seoa; Jeong, Dong-Hoon; Choo, Young-Kug; Bae, Jong Hyang; Kim, Chul Min; Lee, Yeon Hee; Demura, Taku; Lee, Young Koung; et al. (Frontiers in Plant Science, 2022)
Rice cultivation needs extensive amounts of water. Moreover, increased frequency of droughts and water scarcity has become a global concern for rice cultivation. Hence, optimization of water use is crucial for sustainable agriculture. Here, we characterized Loose Plant Architecture 1 (LPA1) in vasculature development, water transport, drought resistance and grain yield. We performed genetic combination of lpa1 with semi-dwarf mutant to offer the optimum rice architecture for more efficient water use. LPA1 expressed in pre-vascular cells of leaf primordia regulates genes associated with carbohydrate metabolism and cell enlargement. Thus, it plays a role in metaxylem enlargement of the aerial organs. Narrow metaxylem of lpa1 exhibit leaves curling on sunny day and convey drought tolerance but reduce grain yield in mature plants. However, the genetic combination of lpa1 with semi-dwarf mutant (dep1-ko or d2) offer optimal water supply and drought resistance without impacting gain-filling rates. Our results show that water use, and transports can be genetically controlled by optimizing metaxylem vessel size and plant height, which may be utilized for enhancing drought tolerance and offers the potential solution to face the more frequent harsh climate condition in the future.